2020
DOI: 10.1042/bsr20193563
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of corneal sub-basal nerve plexus changes in multiple myeloma patients by confocal laser scanning microscopy

Abstract: Purpose: Confocal laser scanning microscopy (CLSM) is a non-invasive technique for cellular in vivo imaging of the human cornea. CLSM screening was evaluated for early detection of corneal nerve morphology changes and neuropathogenic events in different stage multiple myeloma (MM) patients. As MM patients show disease as well as therapy related neuropathological symptoms CSLM potentially provides a tool for non-invasive early detection of neuropathogenic events. CLSM findings were compared to the severity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(36 reference statements)
1
9
0
Order By: Relevance
“…In vivo CLSM generates surface-parallel images of the native cornea with cellular resolution, and it can be used to image dendritic cells (DCs) as well as nerves from the subbasal nerve plexus (SNP) with high contrast [ 10 ]. Moreover, several studies have shown that SNP changes are not characteristic of one specific corneal pathology but rather reflect non-specific pathological processes that are present in many corneal, ocular, or systemic diseases [ 11 , 12 , 13 ] or arise as a result of a therapy regime, such as that used to treat multiple myeloma [ 14 ] or breast cancer [ 6 , 7 , 8 ]. Thus, time-lapsed in vivo CLSM-based cell imaging of biomarkers such as corneal sensory nerves or DCs could be a promising tool for the early detection of corneal changes in patients.…”
mentioning
confidence: 99%
“…In vivo CLSM generates surface-parallel images of the native cornea with cellular resolution, and it can be used to image dendritic cells (DCs) as well as nerves from the subbasal nerve plexus (SNP) with high contrast [ 10 ]. Moreover, several studies have shown that SNP changes are not characteristic of one specific corneal pathology but rather reflect non-specific pathological processes that are present in many corneal, ocular, or systemic diseases [ 11 , 12 , 13 ] or arise as a result of a therapy regime, such as that used to treat multiple myeloma [ 14 ] or breast cancer [ 6 , 7 , 8 ]. Thus, time-lapsed in vivo CLSM-based cell imaging of biomarkers such as corneal sensory nerves or DCs could be a promising tool for the early detection of corneal changes in patients.…”
mentioning
confidence: 99%
“…Moreover, we learned from their work on CNFL that expanding the mosaic image area stabilizes the CNFL values and decreases the movement variation (23). Currently, there have been a number of reports using wide-field imaging tools to study SNP-related diseases, such as the study of severe diabetic foot deformity by Herlyn et (27), and so on. A significant advantage of the widefield technique is its capacity to offer imaging data with a wider field of view, possibly allowing the physician to analyze identical tissue sections repeatedly (22).…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increased interest in using CSLM, that non-invasive technique as an objective diagnostic tool for peripheral neuropathies due to the capability to acquire high-resolution in vivo images of the densely innervated human cornea [27][28][29]. Also, the evaluation of the subbasal nerve plexus of the cornea has led to a significant rise in CSLM use to help clinicians diagnose various diseases (Figure 3).…”
Section: Subbasal Nerve Plexusmentioning
confidence: 99%